(untitled) (Taipei, Taiwan ROC, 2001)
This book presents common micronutrient deficiencies of major crops grown by small-scale farmers in the Asian and Pacific region. It includes color photos as an aid to identification, and also critical values for laboratory tests of soil samples and plant tissues. Most important, it gives information on how these micronutrient deficiencies can be corrected
Keywords: Crops,Crops,Deficiency diseases in plants; Nutritions,Quality; Asia,Asia,Asia